Problems of the 6th Semester Students in Micro Teaching Class at English Education Department FTIK of UIN SMDD Bukittinggi - Putri, Fabiola Amanda; Melani, Melyann; Reflinda, Reflinda; Roza, Veni (Education Achievement: Journal of Science and Research, 2024)
This research was motivated by the theory that problems of 6th semester micro teaching students in teaching skills. The purpose this research was to analyse whats the students teaching skills in micro-teaching. This research used a qualitative descriptive research design. There were 12 students in the 6th semester as the informants in this research. The instrument used in this research was interview and  observation sheet. There are 8 questions of interview covering the 5 indicatros of the problems micro teaching and There are a total of 40 statements related to teaching skills, covering the 8 basic teaching skills. The analysis of the data was carried out using an interactive model method, and each informant was observed individually. The result of the analysis has been presented in a structured narrative explanation. The result is finding the problems of the 6th semester students in teaching skills and solutions of the problems.